Selling to visiting fans at the expense of home field advantage - Reese, James T., Jr., 1966- (SAGE Knowledge. Cases., 2013)
After eight years on staff, Katie Harris was recently promoted from director of ticket operations to a new position as associate athletic director at Montgomery University (MU). Several months into her new position, Katie is faced with a difficult challenge. Several thousand fans from conference rival Bucks State College (BSC) attended a men's basketball game at the 15,000-seat MU Convocation Center. The large presence of BSC fans did nothing worthy of ejection, but was able to negatively impact the experience for many MU fans. MU's high profile men's basketball coach contacted the director of athletics requesting if something could be done to reduce the impact of visiting fans. Though the coach understands that dealing with opposing fans is part of sport, even on a team's home court, the environment has become a distraction for coaches, players, and many significant athletic department donors who pay premium prices for season tickets. The coach received complaints from numerous supporters indicating that unless something is done they are considering cancelling their season tickets. Though complicated by logistics, financial, and legal consequences, Katie has been asked to research the issue and share recommendations for policy development.